Potential Development of Balinese Water-Control System (Subak) Based Agro-Tourism in the World Cultural Heritage Site of Catur Angga Batukaru - Suamba, I Ketut; Sumiyati, Sumiyati; Tika, Wayan; Sulastri, Sulastri; Agung Keswari Krisnandika, Anak (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
One of the cultural world heritage sites in the cultural landscape in Bali province is the area of Catur Angga Batukaru. The aim of this research is to unearth the potentials which could be developed from the Balinese water-control systems (Subak) in the area of Catur Angga Batukaru. The results of the research show that, at present, there has been 20 water-control systems recorded in the area of Catur Angga Batukaru. The lines go through 19 water-control systems. The kind of tourism which could be developed included: (i) sightseeing tourism, where the tourist walk through the area and enjoy the sightseeing and views of the rice terraces together with some other plantation views in the area. (ii) Spiritual tourism, which located at Tamba Waras Temple, where people come to pray for an abundant of health or a recovery of those who are suffering some medical conditions, and at Muncaksari Temple, where people could come to pray for those who wish to be successful in business and trading. (iii) Trekking tourism, which deemed much suitable for adventurous tourists. The trekking paths would be through some rice field area, plantation, and some river crossing by. The attractions available would include some sightseeing of the local farmers busy in the field, planting red rice, taking care of the irrigation system, working on the soil, planting seeds, cleaning up the plant, and harvesting by using some traditional tools used in the associated culture called “ane-ane”, and lastly, some view of traditional religious ceremony in the rice field area as well as around the water-control system (Subak). All things considered, these potential activities are considered needed to be developed further by the community such as through the water-control system society and the village cultural authorities to be assisted bythe local government training and consultation. Lately, the safari tour has been passing through the area as well. The spiritual tourism at the least has also been developing. However, these circumstances have not been well-organized both by the local authorities and the government in it.